Microplastic Contamination in Well Water in Coastal Area of Jember Regency: Study of Characteristics, Abundance and Potential Causal Factors - Arwikana, Amanda Agustine; Ma’rufi, Isa; Nurika, Globila (JURNAL KESEHATAN LINGKUNGAN, 2025)
Introduction: Sand-textured soil such as coastal makes it easier for microplastics to migrate over longer distances. Kalimalang Hamlet, a coastal area, has a sandy soil texture and most of its people consume untreated dug well water. This condition if it occurs in the long term can cause health problems, such as oxidative stress, metabolic changes, immune dysfunction, and cancer. This study is aimed at analyzing the content, abundance, and causative factors of microplastics in the well water of the community of Kalimalang Hamlet. Methods: This study is a quantitative-research with a descriptive method. Thirty samples of people who consumed water were selected by accidental sampling. Ten wells location was determined using cluster random sampling followed by proportional random sampling. Data analysis used was univariate with crosstab. Results and Discussion: The results showed that 10 dug wells were polluted with microplastics with a total of 188 particles with a size of 0.13-7.24 mm and identified forms of fibers, fragments, filaments. It is estimated that there are 235 microplastic particles per day consumed by the community through dug well water. Well depth, floor, sewerage, and distance from the waste management site have the potential to increase the abundance of microplastics. Conclusion: The distance of the dug well from the sea was not a major factor. This shows the need to implement plastic waste management such as 3R, boiling, and multistage filtration in the dug well water that will be consumed.